Cervical Cancer and its Screening: A Cross-Sectional Study among Married Women in Sankhu, Kathmandu - Rijal, Sita; Rijal, Alisha; Deo, Satish Kumar (Birat Journal of Health Sciences, 2019)
Introduction: Cervical cancer ranks as the most frequent cancer among women between 15 and 44 years of age in Nepal. It is one of the preventable cancers. The effectiveness of cervical cancer screening depends to a great extent on the level of awareness. Objective: The objective of study is to explore the knowledge regarding cervical cancer and its screening and use of Pap smear test as a screening tool amongst the married women in Sankhu, Kathmandu. Methodology: A descriptive, cross-sectional study was conducted in April 2017 using interview guided questionnaire. One hundred and ten married women aged 30-60 years were included in the study to assess knowledge regarding cervical cancer and its screening. Among 110, 85 were eligible for screening tests but only 65 consented and participated in Pap smear tests. Multiple regression analysis was used to find out the association of knowledge and practice of cervical cancer and its screening with various variables. Results: Out of 110 participants, 54.5% belong to age groups 30-40 and mean age was 41.50 years. Though 62.5% knew about cervical cancer and 26.8% knew about pap smear test, only 22.7% participants had undergone cervical cancer screening test previously. Multivariateregression analysis showed that the lower education level was significantly associated with poor knowledge on cervical cancer (Odd ratio: 1.71, 95% Confidence interval 1.10-2.66; p=0.01) and poor practice of its screening (Odd ratio 1.92, 95% Confidence interval 1.27-2.89; p=0.00). Conclusion: The study reveals that education level has significant effect on knowledge and practice of screening tests.